Food science and technology / Geoffrey Campbell-Platt; International Union of Food Science and Technology. - Campbell-Platt, Geoffrey editor
Edited by a world-renowned food scientist with a long career in industry and academia, the revised and updated second edition of Food Science and Technology covers all the core modules of food science and technology degree programs internationally